234k views
0 votes
G(x) = (-5x – 1)(2x + 8) lesser x greater x

G(x) = (-5x – 1)(2x + 8) lesser x greater x-example-1

1 Answer

4 votes

Step-by-step explanation

Step 1

to find the zeros of the funciton means to find the values in x wich makes y=0

then


\begin{gathered} g\mleft(x\mright)=(-5x-1)\mleft(2x+8\mright) \\ 0=(-5x-1)(2x+8) \\ it\text{ is} \\ (-5x-1)=\text{ 0 Equation (1)} \\ or \\ (2x+8)=0\text{ Equation(2)} \end{gathered}

Step 2

solve equation (1)


undefined

User Christopher Perry
by
4.6k points